2015
DOI: 10.1007/s10681-015-1440-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions

Abstract: Vernalization requirement in wheat is determined by allelic variation mainly at three loci, Vrn-A1, Vrn-B1 and Vrn-D1. Up to 2011 only two alleles at the Vrn-D1 locus were known. The dominant allele, now designated as Vrn-D1a, confers spring growth habit, and the other, recessive allele, vrn-D1, is associated with the winter growth habit. Recently, we found an additional dominant allele, Vrn-D1b, associated with the facultative growth habit. As facultative wheat cultivars play an important role in wheat produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…RNase treatment and phenol: chloroform: isoamyl alcohol precipitation was carried out for puri cation of isolated DNA (Sambrook et al 1989). The basic PCR ampli cations were performed in a 20 µL reaction mixture containing 10 µL 2 x Taq PCR Master Mix, 1 µL 50-100 ng µL -1 g DNA, 1 µL 10 p mol lL -1 of each primer and 7 µL sterilized ddH 2 O (Guo et al 2015). The PCR pro le was: Initial denaturation at 94°C for 5 minute, followed by denaturing at 94°C for 1 minute, annealing at 52-60°C for 30s, and extension at 72°C for 30 seconds to 2 minutes, and steps 2-4 were repeated 34 cycles with a nal extension at 72°C for 10 min.…”
Section: Ssr Marker Genotypingmentioning
confidence: 99%
“…RNase treatment and phenol: chloroform: isoamyl alcohol precipitation was carried out for puri cation of isolated DNA (Sambrook et al 1989). The basic PCR ampli cations were performed in a 20 µL reaction mixture containing 10 µL 2 x Taq PCR Master Mix, 1 µL 50-100 ng µL -1 g DNA, 1 µL 10 p mol lL -1 of each primer and 7 µL sterilized ddH 2 O (Guo et al 2015). The PCR pro le was: Initial denaturation at 94°C for 5 minute, followed by denaturing at 94°C for 1 minute, annealing at 52-60°C for 30s, and extension at 72°C for 30 seconds to 2 minutes, and steps 2-4 were repeated 34 cycles with a nal extension at 72°C for 10 min.…”
Section: Ssr Marker Genotypingmentioning
confidence: 99%
“…For each treatment, three plants from each genotype were sampled for observing the developmental morphology of inflorescence using a stereoscopic microscope (Olympus, Tokyo, Japan). Days from sowing to the double ridge stage were used to measure the response to vernalization as described by Guo et al (2015) .…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that allele Vrn-D1a, Vrn-D1b and vrn-D1 were present in 27.3, 20.6 and 52.1 % of the specimens, respectively. Pedigree analysis indicates that Vrn-D1b originated from Chinese landraces (Guo et al, 2015).…”
Section: Variability Of Dominant Alleles Of the Vrn Genes In Spring A...mentioning
confidence: 99%